Case series of probable sporadic Creutzfeldt-Jakob disease from Eastern India - Atanu Biswas; Namrata Khandelwal; Alak Pandit; Arijit Roy; Deb Sankar Guin; Goutam Gangopadhyay; Asit Senapati (Annals of Indian Academy of Neurology, 2013)
Background: Creutzfeldt-Jakob disease is a rapidly progressive, fatal, transmissible neurodegenerative disorder caused by prion protein. It is still considered rare in countries like India. This is probably due to nonavailability of autopsy studies in majority of the center. The recent European diagnostic criterion for sporadic CJD (sCJD) is useful for making an early diagnosis. Objective: To report a series of patients of probable sCJD from a neurology institute of eastern India. Materials and Methods: Patients of rapidly developing dementia fulfilling the diagnostic criteria for sCJD were included. All were investigated in detail to find out any possible treatable cause including electroencephalography (EEG), magnetic resonance imaging (MRI) of brain, and cerebrospinal fluid analysis. Results: A total 10 patients of probable sCJD diagnosed using the European diagnostic criterion between December 2011 and January 2013. The clinical features are consistent with other reported series. While 60% of patients had the classical EEG findings, 100% had typical MRI features. Eight patients died within a mean duration of 4.56 months from the disease onset. Conclusions: The clinical features are similar to other reported series. Our observation raises question about the prevalence of this disease in India which needs more elaborate studies.